Possibilities of GGOI in the Ecuadorian waters affecting by the Humboldt Current derived from the Antarctic Ocean - Naganobu, Mikio; Cuadra, Telmo De la; Dominguez, Mario Hurtado; Romero, Alvaro; Yagi, Masafumi; Kutsuwada, Kunio (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OB] Polar biology, Wed. 5 Dec. / 2F Auditorium, National Institute of Polar Research conference object